KOMUNIKASI INTERPERSONAL PUSTAKAWAN DALAM MEMBERIKAN PELAYANAN KEPADA PEMUSTAKA DI UNIVERSITAS NEGERI I GUSTI BAGUS SUGRIWA DENPASAR - Wayan Ngurah Eka Kurniawan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Librarians are an important part of a school or university. Given that the library is a learning center that functions as an agent of social change that improves the quality of life by meeting the information needs of the community, especially students, it is felt necessary to discuss the interpersonal communication of librarians. The success of a communication depends a lot on the ability and insight of the librarian as the person who conveys the message, who is involved in determining the success or failure of a communication. The existence of a library in an educational environment is an important supporting facility for the implementation of the learning process at the institution. Especially in the university environment as one of the supports in the Tri Dharma of Higher Education, namely education, research, and community service. This article uses a descriptive qualitative research method that is supported by a literature study. This study finds that the Interpersonal communication is needed in the process to achieve the goals of the librarian in the context of the success of the library in fulfilling its overall function. The aspect of fishing with interpersonal communication is the most important aspect. The librarian's interpersonal communication in serving the visitors at the Hindu State University I Gusti Bagus Sugriwa Denpasar looks good, although there are still obstacles in interpersonal communication, especially in conveying a librarian's message which is sometimes not accepted or cannot be understood by those served in the library. This can be overcome by structured team work and trainings that have been carried out